Antiferromagnetism induced by oxygen vacancies in V2O5 polycrystals synthesized by the Pechini method. (6th October 2015) - Dreifus, D; Godoy, M P F; Rabelo, A C; Rodrigues, A D; Gobato, Y G; Camargo, P C; Pereira, E C; de Oliveira, A J A
Abstract: Optical and magnetic properties of V2 O5 polycrystals were investigated through photoluminescence (PL) and magnetization measurements. The PL spectra comprise two main bands attributed to oxygen vacancies and to band-edge-related transitions. The magnetization measurements showed a predominant paramagnetic behavior in the temperature range studied (5 K–300 K) with a superimposed peak around 80 K associated with an antiferromagnetic phase. The temperature dependence of the magnetic results and the relative PL intensity presented a remarkable correlation while in the range of 80–200 K the intensity associated with oxygen vacancies became considerably more intense than band-to-band emissions, the same range in which the antiferromagnetic transition was observed. The observation of an antiferromagnetic phase in V2 O5 was predicted in the literature although this result had not previously been measured experimentally. Raman spectroscopy was used as a complementary technique in order to exclude the presence of spurious vanadium oxide phases in the sample.